Hearing loss and vertigo among COVID-19 patients: a review - Swain, Santosh Kumar (International Journal of Research in Medical Sciences, 2021)
The coronavirus disease 2019 (COVID-19) is an acute respiratory disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The clinical presentations of the COVID-9 patients vary from mild respiratory illness to fatal possible outcomes like death. SARS-CoV-2 infection can cause a wide range of extrapulmonary manifestations including sensory and neural complications like olfactory and/or gustatory dysfunction,otologic manifestations and long-term neurological complications. The association between the COVID-19 infection and hearing loss and vertigo make intuitive sense, give neuropathic manifestations of the inner ear resulting in cochleovestibular symptoms. Hearing loss and vertigo are interesting clinical outcomes associated with COVID-19 infections. Hearing loss and vertigo in COVID-19 patients have not received much attention from medical professionals. COVID-19 infection could have deleterious effects on the inner ear despite patients are asymptomatic. Hearing loss and vertigo play an important role for affecting routine activity and result in invisible handicap of the affected person and psychological solitary confinement. In current COVID-19 pandemic, some patients of COVID-19 are presenting with cochleovestibular symptoms such as hearing loss, vertigo and tinnitus. The proper understanding of the pathophysiology behind the hearing loss and vertigo in COVID-19 infections requires further research.This review article discusses the details of this epidemiology, etiopathology, assessment and management of the hearing loss and vertigo among COVID-19 patients.